The need for a revised lower limit for the 4253H, Twice nonparametric smoother - Janosky, J.E.; Pellitieri, T.R.; Al-Shboul, Q.M. (Statistics & probability letters, 1997)
Velleman and Hoaglin (1981) describe the nonparametric smoother 4253H,Twice which uses a combination of running medians and Hanning to smooth data sequences. Velleman and Hoaglin (1981) suggest that the minimum sample size recommended for this nonparametric smoother is seven. A proof and working example presented here suggest that the recommended minimum data points should be higher than seven.